Gastrointestinal symptom improvement from fiber, STW 5, peppermint oil, and probiotics use—Results from an online survey. (December 2018) - Grundmann, Oliver; Yoon, Saunjoo L.; Mason, Sydney; Smith, Keore
Graphical abstract: Highlights: 90% of GI patients use supplements, 80% consult healthcare provider. Fiber was not perceived as effective for GI symptom relief, only as somewhat effective. Probiotics and STW 5 use were correlated with lowest pain rating. Strong correlation between GI symptom severity, overall health, and quality of life. Abstract: Objectives: Several common supplements are used by a significant number of patients affected by gastrointestinal (GI) disorders to improve symptoms and quality of life. We investigated the impact of GI symptom improvement with the use of fiber, STW 5, probiotics, and peppermint oil in relation to overall GI pain and quality of life via an online survey. Design: We used a cross-sectional, descriptive, correlation design. A Qualtrics online survey was utilized to collect data from January to June 2013 through various websites. Areas evaluated included participant demographics, use of supplements, and gastrointestinal symptom severity. Results: The rate of supplement use among patients with GI disorders was high (90% in past year) and consultation with healthcare providers was reported by 80%. Participants who completed the survey (n = 68) reported a strong correlation between GI symptom severity and overall quality of life (r 2  = 0.8682, p < 0.001). The use of fiber improved GI symptom severity while both STW 5 and probiotics were linked to specific improvements. Conclusions: Persons with chronic GI disorders often choose the complementary use of common supplements to mitigate GI symptoms and consult with their healthcare providers frequently. The use of STW 5 and probiotics specifically is linked to overall reduction in GI symptoms and improvement of quality of life.